Meios para análise da composição florística de áreas verdes públicas dimensionalmente diferentes (Terr@ Plural, 2020)
To manage the tree patrimony of public spaces, qualified information on the importance of trees must be provided. We evaluated phytosociological description procedures applied to dimensionally different gardens, testing the importance of the crown area and the overall quality of the trees. We observed changes in the importance of the species, according to the method tested. The best method for phytosociological analysis of public green areas was the one that determined the cover value of the species from the dominance parameter, described by the crown area, and from the performance index of the species, in detriment of density parameter that is traditionally used.
Keywords: Public gardens; Urban forest; Urban forestry; Urban green infrastructure.